Assessment of Nurses' Knowledge, Attitudes, And Willingness Towards Organ Donation: A Cross- Sectional Study at Tibebe-Ghion Specialized Hospital, Bahir Dar, Ethiopia, 2023 - Tamre, Sosina; Tamir, Yeshimebet; Biresaw, Henok; Enyew, Alamirew; Gashaw, Asnake; Adal, Ousman; Mulatu, Sileshi; Berie, Gebrehiwot; Abebe, Mengistu; Tazeb, Wubet; Kibret, Gebremeskel (Journal of Clinical and Practical Nursing, 2025)
Objective To assess knowledge, attitude and willingness towards organ donation of nurses in Tibebe-Ghion Specialized Hospital, Bahir Dar, Ethiopia, 2023. Method A hospital based cross-sectional study was conducted from March 1 to May 30, 2023, using a census of all eligible nurses (N=215). Data were collected with a structured questionnaire adapted from validated tools. Binary logistics regression was used to identify factors associated with willingness to donate, with results presented as adjusted odds ratios with 95% confident intervals. Results The overall response rate of this study was 98% (n=206). The mean age was 29.5 (±4.8) years, and 55.8% were male. Overall, 61.7% (95% CI: 54.9-68.5) of nurses had good knowledge, and 45.6% (95% CI: 38.8-52.5) had a favorable attitude. In multivariable analysis, female sex (AOR=3.50, 95% CI: 1.18-3.92, p<0.001) and greater years of experience (AOR=2.15, 95% CI: 1.18-3.92, p=0.012) were independent predictors of willingness. Conclusion While a majority of nurses were willing to donate organs, significant gaps in knowledge and legal awareness persist. Female nurses and those with more experience were more willing to donate. Targeted educational interventions are recommended to address knowledge deficits and foster a more supportive environment for organ donation advocacy.
Keywords: Knowledge; Attitude; Willingness; Nurse; Organ donation